Into the void: ECM fungal communities involved in the succession from rockroses to oak stands - Ignacio Sanz-Benito; Tim Stadler; Olaya Mediavilla; María Hernández-Rodríguez; Juan Andrés Oria-de-Rueda; Tatek Dejene; József Geml; Pablo Martín-Pinto (Scientific Reports, 2023)
Abstract Oak forests accompanied by Cistus species are a common landscape in the Mediterranean basin. It is argued that Cistus dominated fields serve as recruitment areas for Quercus seedlings, as they help in the transmission of the fungal community through vegetative succession in these ecosystems. To test these assumptions, we analyzed the fungal community in terms of its richness and composition, taking into account the effects of host (Oaks vs. Cistus) and forest structure, mainly based on age. Edaphic variables related to the different structures were also analyzed to examine how they evolve through succession and relate to shifts in the fungal community. No differences in fungal richness were observed between old Cistus stands and younger Quercus, while a brief increase in ECM richness was observed. Community composition also showed a greater overlap between old Cistus and young Quercus stands. We suggest that the most important step in fungal transfer from one host to another is the shift from the oldest Cistus fields to the youngest Quercus stands, with the genera Amanita, Cortinarius, Lactarius, Inocybe, Russula, and Tomentella probably playing a major role. In summary, our work has also revealed the network of fungal community structure in the succession of Cistus to Oak stands, it would suggest that the fungi share niches and significantly enhance the ecological setting of the transition from Cistus to Oak stands.